Deciphering the Semiotic Landscape of Love in Lana Del Rey's 'Mariners Apartment Complex' Song Lyrics - Andres, Salva de Shauma (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2024)
This research paper presents an analysis of Lana Del Rey's song "Mariners Apartment Complex" through the lens of semiotics, using Ferdinand de Saussure's theory to explore the complex signification and interpretation of love in the song's lyrics. This research uses a qualitative approach, focusing on identifying signifiers and signs, and interpreting each verse of the song. The results of the analysis show that the song is rich in messages that convey the power of love, as experienced by a woman. Themes of heartbreak and lovesickness are interwoven throughout the lyrics, showcasing Lana Del Rey's portrayal of a woman deeply invested in deep and unwavering affection. This research highlights the complexity and depth of emotions expressed in the song, highlighting the multifaceted nature of love as a central theme.